2016
DOI: 10.1128/jb.00800-15
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of the Thiol-Disulfide Oxidoreductase SdbA Activates the CiaRH Two-Component System, Leading to Bacteriocin Expression Shutdown in Streptococcus gordonii

Abstract: Streptococcus gordonii is a commensal inhabitant of the human oral cavity. To maintain its presence as a major component of oral biofilms, S. gordonii secretes inhibitory molecules such as hydrogen peroxide and bacteriocins to inhibit competitors. S. gordonii produces two nonmodified bacteriocins (i.e., Sth 1 and Sth 2 ) that are regulated by the Com two-component regulatory system, which also regulates genetic competence. Previously we found that the thiol-disulfide oxidoreductase SdbA was required for bacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 69 publications
(110 reference statements)
1
15
0
Order By: Relevance
“…Previously, we found that expression of the two-component signalling system CiaRH is upregulated in the ΔsdbA mutant [19]. Although the role of CiaRH in biofilm formation by S .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Previously, we found that expression of the two-component signalling system CiaRH is upregulated in the ΔsdbA mutant [19]. Although the role of CiaRH in biofilm formation by S .…”
Section: Resultsmentioning
confidence: 99%
“…CiaRH represses the ComDE quorum sensing system in the ΔsdbA mutant by inhibiting production of the CSP autoinducer [19]. Accordingly, de-repression of ComDE can be achieved in two ways: (1) inactivate the CiaRH system or (2) expose cells to exogenous CSP [19].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations